Local Adaptation of Bitter Taste and Ecological Speciation in a Wild Mammal - Jiao, Hengwu; Wang, Qian; Wang, Bing-Jun; Li, Kexin; Lövy, Matěj; Nevo, Eviatar; Li, Qiyang; Su, Wenchuan; Jiang, Peihua; Zhao, Huabin (Molecular biology and evolution, 2021)
Sensory systems are attractive evolutionary models to address how organisms adapt to local environments that can cause ecological speciation. However, tests of these evolutionary models have focused on visual, auditory, and olfactory senses. Here, we show local adaptation of bitter taste receptor genes in two neighboring populations of a wild mammal-the blind mole rat Spalax galili-that show ecological speciation in divergent soil environments. We found that basalt-type bitter receptors showed higher response intensity and sensitivity compared with chalk-type ones using both genetic and cell-based functional analyses. Such functional changes could help animals adapted to basalt soil select plants with less bitterness from diverse local foods, whereas a weaker reception to bitter taste may allow consumption of a greater range of plants for animals inhabiting chalk soil with a scarcity of food supply. Our study shows divergent selection on food resources through local adaptation of bitter receptors, and suggests that taste plays an important yet underappreciated role in speciation.
Keywords: savci; Spalax; fyziologická adaptace; Genetic Speciation; ecological speciation; Taste; chuť; Animals; vznik druhů (genetika); functional assay; zvířata; Mammals; local adaptation; bitter taste; Adaptation, Physiological